TINJAUAN SEJARAH FATWA KEAGAMAAN ULAMA PERSIS PADA AWAL ABAD KE-XX (STUDI KASUS PONPES PERSIS BANGIL PASURUAN JAWA TIMUR) - , DWI SUSANTO, Prof. Dr. Joko Suryo, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research focuses on comprehensive explanation on one of respectable religious institution in the modern Islamic thought in the history of Indonesia. In the era that spirit of jihad and ijtihad was the most essential part of their noble objective, i.e. the unity of thought, feeling and voice of Islam, Persis ( the union of Islam) held their firm religious Puritanism from all bidâah (heterodox) takhayul (imaginary thinking) and khurafat (magics). This trend was reflected in their fatwas (respon that related to legal system on every aspects of life) This research is based on legal system in muslim law school point of view, but the author emphasize on âhow Persisâ scholar (ulama) exercised their legal power to issue personal opinion (ijtihad) and legal fatwa through out the history of this religious movement. This subject will be discussed in their historical contex with sosio-intellectual history approach. Each of legal fatwa that was issued mapped in the matic and discussed accordingly to draw systematic explanation on Islamic legal thought established by Persis.. in addition to know the urgence and relation between ijtihad and fatwas. In bref, this research concludes that ijtihad, as one of dynamic factor in Islamic jurisprudence and fatwa have mutual relationship and important role for ummahâs every day life, because of its role as response to every day life, fatwa develops invaluable docement in muslimâs intellectual legacy.